The Evaluation of Implementing The Al-Islam, Kemuhammadiyahan and Arabic (ISMUBA) Curriculum: A Subjective Phenomenological Study - Idayani, Idayani; Wardiah, Dessy; Mahasir, Mahasir (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The religious education program in the process of implementation based on the ISMUBA Curriculum is a typical curriculum belonging to the Muhammadiyah school, which is oriented towards increasing faith, taqwa, and noble morals. This principle is tried to be implemented and realized by SMA Muhammadiyah 1 Palembang in daily programs and learning activities, which are contained in the Al-Islam, Kemuhammadiyahan and Arabic (ISMUBA) curriculum. The focus of the research is on Evaluation of the implementation of the AL-Islam, Kemuhammadiyahan and Arabic (ISMUBA) curriculum. This research was conducted at SMA Muhammadiyah 1 Palembang City. The subjects of the study were the principal, vice principal for curriculum, vice principal for ISMUBA (ISMUBA teachers) in Muhammadiyah 1 Palembang as well as the Palembang City Education Council, students were also not spared in data collection. Data collection techniques are carried out by observation, interviews, and documentation. Data analysis techniques are carried out using the triangulation method which aims to describe, describe, explore and describe the implementation of ISMUBA education in Muhammadiyah 1 High School Palembang.